Employee assistant services (EAS) handbook based on teachers' expectations and perceptions towards help-seeking through counselling - Nurhafizah Binti Yaacob (Universiti Sains Islam Malaysia, 2024)
Employee Assistance Services (EAS) also known as Employee Assistance Program (EAP) plays the role as the medium of helping employees in both work-life and home-life challenges that might interfere the employees’ job performance. The services in EAS offer assistance through consultation, counseling, coaching and seminar related on family and marital issues, career development, industrial relation issues, mental and also physical health. An explanatory study has been conducted among the teachers in the national daily schools in District G, Selangor through four (4) phases of mixed-method research. The research objectives of this study were analysed phase by phase. In Phase I, a quantitative research was conducted to identify the teachers’ demographic background and their challenges in work-life and homelife. This phase also identifies the teachers’ expectations toward the EAS as the medium of workplace wellness program and their perceptions toward help-seeking through counseling services. The respondents’ expectations have shown that enhancement on the existing practice of counseling services is needed on the aspects of the type of services, procedures, referral systems and meet-up location while their perceptions’ toward help-seeking through counseling services have shown that the respondents’ self-stigma, social stigma, emotional openness and anticipated risk & utility were rated at the moderate level. In Phase II, a qualitative research was conducted with the key stakeholders based on the data gathered in Phase I. Through focus group discussions and in-depth interviews, the most suitable criteria of the EAS structure was suggested which followed by the Internal EAS Handbook development in Phase III. To identify its effectiveness and participant’s satisfaction, a pilot Internal EAS was conducted in Phase IV. Through this phase, quantitative and qualitative approaches were conducted as the participants’ pre and post-perceptions toward helpseeking through counseling services were tested. The major findings of the test have proven to be statistically significant and highly improved participants’ self-stigma and social stigma by decreasing both stigmas toward help-seeking through counseling. Participants’ emotional openness and anticipated risk & utility have also proven to be positively impacted and statistically highly significant. The percentage values of the EAS satisfaction among the participants also found to be positively high toward the pilot Internal EAS. This study also provides recommendation for future research of its kind.